CHITOSAN - COPPER / STRONTIUM COMPOSITE MEMBRANE FOR BONE REGENERATION APPLICATION (MSW Management Journal, 2026)
The major source of chitosan CS a partly deacetylated form of chitin is the exoskeleton of crustaceans. Due to its availability adaptability and distinctive properties such as biodegradability biocompatibility non toxicity hydrophilicity antibacterial and antifungal characteristics and wound healing benefits it stands out among other biomaterials. Since the past few decades chitosan based bioactive polymers have been extensively employed in bone regeneration. Well known areas of tissue engineering utilizing chitosan for biomaterial development include cartilage bone intervertebral disc blood vessel corneal regeneration skin tissue fixation and periodontal tissue engineering. The aim of the study was to evaluate a chitosan copper and strontium composite membrane for bone regeneration applications. Chitosan CS from shrimp shells degree of deacetylation 75 percent and collagen Col type I insoluble from bovine Achilles tendon were purchased from Sigma Aldrich. Hydroxyapatite HA was synthesized in our laboratory following the reaction 10Ca OH2 plus 6 NH4 2HPO4 gives Ca10 PO4 6 OH2 plus 12NH4 OH plus 6H2O. Chitosan membranes CS were prepared by solvent casting method. Chitosan solution was obtained by dispersing 1.5 percent weight by volume in an aqueous solution of acetic acid at 2 percent volume by volume. The solution was mechanically stirred until complete solubilization. After that 25 grams of solution was poured into Petri dishes diameter 8.2 cm and dried at room temperature. Using the solvent casting approach composite membranes of chitosan and collagen chitosan and hydroxyapatite and chitosan collagen and hydroxyapatite were successfully prepared.